Экологическая оценка хлората как побочного продукта при обеззараживании диоксидом хлора сточных вод - Петренко, Н.Ф.; Мокиенко, А.В.; Дятлов, С.Е. (Актуальні проблеми транспортної медицини, 2011)
Надано результати екологічної оцінки хлорату як побічного продукту при знезараженні води діоксидом хлору. Висловлено думку про необхідність продовження досліджень і розробки безпечного рівня хлорату для води водойм із включенням у відповідні нормативні документи. It is presented results ecological assessment of chlorate as by-product at disinfection of water by сhlorine dioxide. The opinion on necessity of continuation of researches and working out of safe level of chlorate for water of reservoirs with incorporation in the conforming standard documents is expressed.